ANALISIS PELAKSANAAN AKAD MURABAHAH MENURUT FATWA DSN MUI NO:04/DSN-MUI/IV/2000 TENTANG MURABAHAH DI KOPERASI SYARIAH MASJID BESAR TEGALKALONG SUMEDANG - Abdul Hamid; Fitri Syifa Fauziah (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2020)
The purpose of this study was to see the theoretical and practical application of the Murabahah contract at the Tegalkalong Large Mosque Sharia Cooperative. This research uses a qualitative approach with a study method and collects detailed and in-depth information using several data procedures over a certain period. The results of this study indicate that in general the practice of the Murabahah contract at the Tegalkalong Grand Mosque Sharia Cooperative is in accordance with the MUI DSN Fatwa NO: 04 / DSN-MUI / IV / 2000 concerning Murabahah. However, there are 2 (two) points in the fatwa provisions regarding murabahah that are not in accordance with the practices carried out by the Tegalkalong Grand Mosque Sharia Cooperative, namely, the purchase of goods is represented by members, and members who buy goods on their own behalf, not on behalf of the cooperative. and when the cooperative performs a murabahah contract, at the same time the cooperative that carries out the wakalah contract because the purchase of goods is represented by the member and the member buys goods that have been agreed upon by themselves, this means that the murabahah contract is carried out before the goods become the property of the cooperative.